2006
DOI: 10.1097/01.fpc.0000204994.99429.46
|View full text |Cite
|
Sign up to set email alerts
|

Search for an association between the human CYP1A2 genotype and CYP1A2 metabolic phenotype

Abstract: The genotype responsible for more than 60-fold interindividual differences in human hepatic CYP1A2 constitutive expression is not understood. Resequencing the human CYP1A1_CYP1A2 locus (39.6 kb) in five major geographically isolated subgroups recently led to the identification of 85 single nucleotide polymorphisms (SNPs), 57 of which were double-hit SNPs. Here, we attempted to correlate the CYP1A2 genotype with a metabolic phenotype. We chose 16 SNPs (all having a minor allele frequency > or =0.05 in Caucasian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
72
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 43 publications
3
72
0
4
Order By: Relevance
“…For some metabolic enzymes, this can be predicted by genotype; for others, such as P450 1A2, the genotype does not allow for prediction of phenotype [4]. Given the role of P450 1A2 in metabolism of several important pharmaceutical drugs and in activation of chemical carcinogens, there is great interest in methods to determine an individual's P450 1A2 phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For some metabolic enzymes, this can be predicted by genotype; for others, such as P450 1A2, the genotype does not allow for prediction of phenotype [4]. Given the role of P450 1A2 in metabolism of several important pharmaceutical drugs and in activation of chemical carcinogens, there is great interest in methods to determine an individual's P450 1A2 phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…However, prediction of metabolic phenotype based on genotype with P450 1A2 has proven to be challenging and is an area of research that generates continued controversy. Multiple studies have shown that genotype for P450 1A2 does not appear to result in a specific interindividual variation or phenotype of P450 1A2 metabolic activity [4,12,24]. In the end, interindividual differences in phenotypic P450 1A2 activity still remain of great interest because of the connection with drug metabolism and carcinogen metabolism.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…9 The spacer sequence may contain distinct regulatory regions of each gene or, alternatively, the regulatory regions of both genes. 10 CYP1A1 is mainly expressed in extrahepatic tissues, whereas CYP1A2 is almost exclusively expressed in the liver, representing B15% of its total CYP content. 11 CYP1A enzymes catalyze the bioactivation of pre-carcinogens, such as polycyclic aromatic hydrocarbons (CYP1A1), as well as aromatic and heterocyclic amines (CYP1A2).…”
Section: Introductionmentioning
confidence: 99%